Analisa Pengembangan Klaster Industri Batik Di Madura - Mayvani, Titov Chuk's; Sutikno, Sutikno; Oktavianti, Henny (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Madura is the tenth largest creative economy in East Java Province, especially in the batik creative industry. The fesyen (batik) industry is one of the largest sectors contributing to the regional economy of East Java Province. Therefore, the aim of this research is to analyze and identify subsector groups of the batik industry based on indicators from cluster theory so that it is hoped that further development strategies can be formed regarding batik industry clusters in Madura. The results of this research show that the batik industry in Madura is classified into active clusters and dynamic clusters. Strategies that can be developed to increase the classification of industries included in active clusters to become dynamic clusters are: obtained from the results of SWOT calculations, namely 1) Mapping local resource potential; 2) Development of economic/industrial specialization; 3) Adoption and mastery of renewable technological developments in production activities and increasing business collaboration networks; 4) Expanding access to information exchange.